Friendship and allegiance in eighteenth-century literature : the politics of private virtue in the age of Walpole - Jones, Emrys, 1984- (Palgrave studies in the enlightenment, romanticism and the cultures of print, 2013)
"The concept of friendship has long been central to the field of eighteenth-century literary studies, not least because it was presented by the era's own authors as an essential aspect of their literary identities. For writers like Alexander Pope and Jonathan Swift, being known as a good friend was just as important as gaining literary reputation.Friendship and Allegiance builds on recent scholarly interest both in friendship itself and more broadly in the relationship between privacy and publicity in the eighteenth century. It investigates how the idea of personal friendship could be distorted by its role in public discourse and whether friendship's value or meaning can ever be securely established in the midst of wider political, social and cultural debates. The book offers new ways of thinking about eighteenth-century friendship and about the prominent authors of the time who attempted to make sense of it"--